The economics of insurgency in the Mekong Delta of Vietnam - Sansom, Robert L. (M.I.T. Press, 1970)
Much of the material for this book was obtained through interviews with farmers, landlords, moneylenders, and laborers in the Delta. The author discusses general economic conditions in the area, agricultural productivity, capital and labor, land tenure, fertilizer use, and a subsistence innovation involving the use of an intermediate technology. The analysis focuses not only on the theoretical issues of development economics, such as disguised unemployment, innovation, and investment decisions, but also upon their larger social and political implications.